Evaluation of a Prototype Tool for Communicating Body Perception Disturbances in Complex Regional Pain Syndrome - Turton, Ailie; Palmer, Mark; Grieve, Sharon; Moss, Tim; Lewis, Jenny; McCabe, Candy (Frontiers in Human Neuroscience, 2013)
Patients with Complex Regional Pain Syndrome (CRPS) experience distressing changes in body perception. However representing body perception is a challenge. A digital media tool for communicating body perception disturbances was developed. A proof of concept study evaluating the acceptability of the application for patients to communicate their body perception is reported in this methods paper. Thirteen CRPS participants admitted to a two week inpatient rehabilitation program used the application in a consultation with a research nurse. Audio recordings were made of the process and a structured questionnaire was administered to capture experiences of using the tool. Participants produced powerful images of disturbances in their body perception. All reported the tool acceptable for communicating their body perception. Participants described the positive impact of now seeing an image they had previously only imagined and could now convey to others. The application has provided a novel way for communicating perceptions that are otherwise difficult to convey.